Kingdom hearts : chain of memories. 1 - Amano, Shiro; Terriqez, Deida; Estacio, Mike. (Los Angeles, Calif. : Tokyopop, 2006)
In this sequel series to the first Kingdom hearts manga series, Sora, Donald and Goofy search for their friends Riku and King Mickey, who are trapped inside Kingdom Hearts.
At head of title: Disney Square Enix.
Keywords: Plurality of worlds -- Comic books, strips, etc. -- Juvenile fiction; Magic -- Comic books, strips, etc. -- Juvenile fiction; Good and evil -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Donald Duck (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Goofy (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Jiminy Cricket (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Fantasy comic books, strips, etc. -- Juvenile literature; Graphic novels -- Juvenile literature